County Counsel Softball Team at Oakland A's vs. Twins Baseball Game - Watkins, Howard::::::::: (1989)
Maureen Walsh, Howard Watkins, Adam Watkins, ?, Pam Stone, Greg Kamptner, ?, John Slutter and Bill Smith standing